Ergodicity of the mapping class group action on super-maximal representations - Maret, Arnaud (Arxiv, 2022)
This note investigates the dynamics of the mapping class group action on the character variety of super-maximal representations of the fundamental group of a punctured sphere into PSLp2, Rq, discovered by Deroin and Tholozan. We apply symplectic methods developed by Goldman and Xia to prove that the action is ergodic.
Online veröffentlicht am 10. Dezember 2020
Gesehen am 10.01.2024